Creating the Perfect Blend: Lifestyle, Ambiance, Product Variety, and Customer Experience Influencing Revisit Intention - Sindi Febrianti; Nur Laili Fikriah (Jurnal Computech & Bisnis (e-journal), 2025)
The rising global demand for coffee, including in Indonesia, has significantly contributed to the growth of the coffee shop industry, which has become an integral part of modern lifestyles. This study examines how lifestyle, café ambiance, product variety, and customer experience influence the intention to revisit Critasena Coffee Shop in Malang. The research was conducted across five districts in Malang City: Klojen, Lowokwaru, Blimbing, Kedungkandang, and Sukun. Using a quantitative approach and causal design, this study collected data from 180 respondents through online and offline questionnaires using a 5-point Likert scale. Participants were selected using purposive sampling method. Data analysis was conducted with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS software version 4.0.. The findings reveal that lifestyle, café atmosphere, and customer experience significantly and positively affect revisit intention, whereas product variety does not have a significant impact. This research provides practical contributions for coffee shop entrepreneurs in designing strategies to increase customer loyalty, as well as theoretical contributions in enriching the literature related to consumer behavior in the coffee shop industry.